Genetically designed biomolecular capping system for mesoporous silica nanoparticles enables receptor-mediated cell uptake and controlled drug release. Issue 15 (29th March 2016) - Datz, Stefan; Argyo, Christian; Gattner, Michael; Weiss, Veronika; Brunner, Korbinian; Bretzler, Johanna; von Schirnding, Constantin; Torrano, Adriano A.; Spada, Fabio; Vrabel, Milan; Engelke, Hanna; Bräuchle, Christoph; et al.
Abstract : We describe a novel enzyme-based cap system for mesoporous silica nanoparticles combined with bio-orthogonal click chemistry. Abstract : Effective and controlled drug delivery systems with on-demand release and targeting abilities have received enormous attention for biomedical applications. Here, we describe a novel enzyme-based cap system for mesoporous silica nanoparticles (MSNs) that is directly combined with a targeting ligand via bio-orthogonal click chemistry. The capping system is based on the pH-responsive binding of an aryl-sulfonamide-functionalized MSN and the enzyme carbonic anhydrase (CA). An unnatural amino acid (UAA) containing a norbornene moiety was genetically incorporated into CA. This UAA allowed for the site-specific bio-orthogonal attachment of even very sensitive targeting ligands such as folic acid and anandamide. This leads to specific receptor-mediated cell and stem cell uptake. We demonstrate the successful delivery and release of the chemotherapeutic agent Actinomycin D to KB cells. This novel nanocarrier concept provides a promising platform for the development of precisely controllable and highly modular theranostic systems.